Improving Beginning Reading Abilty for Dylexian Children through Letter Puzzle Media in Class IV SDN 08 Sarilamak - Yora Kurniawan; Damri Damri (Edumaspul: Jurnal Pendidikan, 2022)
This research is motivated by the problems that exist in the field, namely a child with learning difficulties who have difficulty in reading (dyslexia) who is in fourth grade at SD N 08 Sarilamak. Children have problems reading words with KV-KVK patterns so that children cannot follow the lessons at school. This study aims to improve children's ability to read early, especially reading words with a KV-KVK pattern. This research is an experimental study in the form of single subject research (SSR) with an A-B-A research design, the subjects in this study are dyslexic children with problems in early reading. especially in reading words with KV-KVK pattern. Data collection techniques in this study used test instruments and documentation of the ability to read words with KV-KVK patterns in children. Data analysis techniques in this study used analysis techniques under conditions and analysis between conditions. Keywords: Letter Puzzle, Beginning Reading, Dyslexia